Barriers of Implementing Action Research among Malaysian Teachers - Shanmugam, S. Kanageswari Suppiah; Lee, Shok Mee (Universiti Putra Malaysia Press, 2017)
Action research is instrumental in enhancing teachers’ professional development.Therefore, this study attempts to identify the challenges faced by Malaysian teachers in conducting action research in their schools and ensure its successful implementation.A total of 34 mathematics and science teachers participated in a focus group discussion.Thematic analyses indicate that the challenges can be classified as the ‘S Factor’ (school factor) and the ‘T Factor’ (teacher factor).The key challenges were found to be lack of research culture in schools, which have led to a series of other challenges, and teachers’ lack of confidence due to limited scaffolding received in acquiring research-based knowledge and skills.